ANALISIS KAPASITAS TIANG PANCANG TERHADAP BEBAN IMPAK PADA STRUKTUR PELINDUNG PILAR JEMBATAN - Kusuma Whardani, Putri Nurul; Agistin, Veriza; Nurdin, Ade; Yudhagama, Fadhol (Journal of Science and Engineering, 2025)
The Batanghari I Bridge in Jambi Province is a strategic piece of infrastructure that spans a busy river shipping lane frequently traversed by heavily loaded coal barges. The bridge's pier protection structures (fenders), particularly at piers 5 and 6, have experienced multiple direct collisions with barges. This raises concerns about the pile foundation system’s capacity within the fender structure to withstand impact loads. This study aims to analyze the structural capacity of pile foundations under barge impact loads using a numerical approach. The method employed involves mathematical modeling using the MIDAS Civil software, with input data consisting of secondary sources such as barge specifications, soil data, and the geometry of the fender structure. The impact load is calculated based on the provisions of the Ministry of Public Works and Housing Circular No. 12/SE/M/2015, using a design barge with a length of 270 feet and a full load of 5,200 tons. The impact energy is calculated at 39,169.22 Joules, resulting in a lateral impact force of 472.95 kN, which increases to 756.72 kN after applying the live load factor. The modeling results indicate that a D1000 steel pile with a length of 30 meters possesses sufficient structural capacity to withstand the impact load from the design barge. The study concludes that the existing fender structure remains viable for continued use.